Career Development and Job Satisfaction - Fahed-Sreih, Josiane (IntechOpen, 2020)
This book, Career Development and Job Satisfaction, not only looks at how employees can develop their careers and create career paths that are meaningful for their lives, it also looks at keeping employees satisfied with their jobs.This book highlights how to work with the millennial generation and being able to motivate them and guide them through their careers. It presents case studies on satisfaction and career planning. The function of human resource management has an important implication on the performance of the whole organization and giving it acute attention can enhance the performance of the business.